A review on performance of waste materials in self compacting concrete (scc) - Ismail, Isham; Jamaluddin, Norwati; Shahidan, Shahiron (PENERBIT UTM PRESS, 2016)
Self-compacting concrete (SCC) was first developed in late 80’s in Japan. SCC is well known for its self-consolidation and able to occupy spaces in the formwork without any vibration and become new interesting topic in Construction and Building Materials Research. There were various SCC researches that have been carried out in Turkey, Malaysia, Thailand, Iran, United Kingdom, Algeria, and India.The aim of this review is to summaries the alternative material used in the mix design from 2009 to 2015 through available literature. It hascommon materials such as Limestone Powder (LP), Fly Ash (FA), Silica Fume and Granulated Blast Furnace Slag (GBFS). While there are many alternative or recycled material can be used in producing SCC. This review only focus on waste material fromMarble Powder (MP), Dolomite Powder (DP), Crump Rubber (CR), Recycled Aggregate (RA) and Rise Husk Ash (RHA).Each type of materialshassimilarity effect in fresh and hardened state of SCC. Therefore, this paper will provide significant and useful information to those new to SCC and fellow researchers for future studies on SCC.